A Literary Review on Sandal Wood: Santalum Album Linn - Miraaj, R.; Sathiyaseelan, V. (Charithra Malika Kerala Historical and Educational Cultural Research Museum, Amaravila, Thiruvananthapuram, 2024)
The Siddha Medicine is the ancient and mother of traditional medical system which is practiced in Sri Lanka and Tamil speaking region of the world. The system mostly focused to treat diseases by using combination of medicinal plants, metals & minerals and product of animal kingdom to prepare Siddha drug formulations. In medicinal plants wood has a special place in Siddha system which is the most common part used in medicine preparation This review study aimed to develop scientific biography evidence for forest woods which are used in Siddha system and data for this study were collected from related Siddha traditional text books and research publications on websites from July to September 2024. Santalum album L. belonging to family of Santalaceae, is a small tropical tree, is commonly well-known as sandalwood, and Chandanam. The plant is considered as the holiest, valuable and commercially important tree which is also used as timber in Srilanka. The plant is well known for its exclusive and characteristic perfume. Also, this plant is considered sacred and its importance and usage are also mentioned in Vedas, Puranas of Hinduism and Buddhism. The heartwood of the plant is very expensive and it has great commercial value in the local and global market as it is enhanced with fragranced essential oil. The aromatic essential oil of the plant is used in various cosmetics purpose, perfume industry, food products, aroma therapy and pharmaceutical industries. Traditionally, the plant is used in various medicinal systems such as Siddha, Ayurveda, Unani and Traditional doctors to cure diseases like gastric irritability, jaundice, dysentery, used as a tonic for liver, heart and Brain. In Siddha system, the sandalwood plant is used as an expectorant, diuretic, astringent, stimulant, coolant, sedative, demulcent antioxidant, anticancer, anti-inflammatory, antiviral, antibacterial, antifungal, hepato protective and cardio- protective properties. The fragrant parts of sandalwood oil constitutes of a- and ẞ santalols. The extensive removal and unawareness of S. album over the past century led to increased vulnerability to extinction of the plant so it is procured in the International Union for Conservation of Nature (IUCN).
Keywords: Siddha Medicine; Santalum album; sandalwood; Esssentialoil; Santalol